Deciphering shigella invasion of epithelial cells - Sansonetti, Philippe (Henry Stewart Talks, 2009)
A genetic and molecular analysis of the mechanisms used by the bacterial pathogen Shigella to invade epithelial cells, Identification of bacterial effectors of invasion, mode of delivery, nature of cell targets, How a bacterial pathogen like Shigella causes the rupture and inflammatory destruction of the intestinal epithelial barrier, How it also regulates the inflammatory response, The accent is on identification of the bacterial effectors and their cellular targets